Answer

Verified

435.9k+ views

Hint: Rationalize the identity so that the evaluation becomes simple. Also, the standard identities can be easily used.

We have the given quadratic equation as:

$\dfrac{{5 + x}}{{5 - x}} - \dfrac{{5 - x}}{{5 + x}} = 3\dfrac{3}{4}$

By rationalization, we get,

$ \Rightarrow \dfrac{{5 + x}}{{5 - x}}\left( {\dfrac{{5 + x}}{{5 + x}}} \right) - \dfrac{{5 - x}}{{5 + x}}\left( {\dfrac{{5 - x}}{{5 - x}}} \right) = \dfrac{{15}}{4}$

$ \Rightarrow \dfrac{{{{(5 + x)}^2} - {{(5 - x)}^2}}}{{(5 + x)(5 - x)}} = \dfrac{{15}}{4}$ … (1)

Now, we know the identities,

${(a + b)^2} = {a^2} + {b^2} + 2ab$

${(a - b)^2} = {a^2} + {b^2} - 2ab$

$({a^2} - {b^2}) = (a - b)(a + b)$

Therefore, by using these identities, we get the equation (1) as

$ \Rightarrow \dfrac{{({{(5)}^2} + 10x + {x^2}) - ({{(5)}^2} - 10x + {x^2})}}{{({{(5)}^2} - {{(x)}^2})}} = \dfrac{{15}}{4}$

$ \Rightarrow \dfrac{{(25 + 10x + {x^2} - 25 + 10x - {x^2})}}{{(25 - {x^2})}} = \dfrac{{15}}{4}$

$ \Rightarrow \dfrac{{20x}}{{(25 - {x^2})}} = \dfrac{{15}}{4}$

Multiplying both sides by $\dfrac{1}{5}$ , we get,

$ \Rightarrow \dfrac{{20x}}{{(25 - {x^2})}} \times \left( {\dfrac{1}{5}} \right) = \dfrac{{15}}{4} \times \left( {\dfrac{1}{5}} \right)$

$ \Rightarrow \dfrac{{4x}}{{(25 - {x^2})}} = \dfrac{3}{4}$

$ \Rightarrow (4x) \times 4 = 3 \times (25 - {x^2})$

$ \Rightarrow 16x = 75 - 3{x^2}$

$ \Rightarrow 3{x^2} + 16x - 75 = 0$

$ \Rightarrow 3{x^2} + 25x - 9x - 75 = 0$

$ \Rightarrow x(3x + 25) - 3(3x + 25) = 0$

$ \Rightarrow (x - 3)(3x + 25) = 0$

Now, either $(x - 3) = 0$

$\therefore x = 3$

Or $(3x + 25) = 0$

$\therefore x = \dfrac{{ - 25}}{3}$

Hence, the roots are $3,\dfrac{{ - 25}}{3}$.

So, the required solution is (a) True.

Note: In order to solve these types of questions, an adequate knowledge of standard identities is needed, after substituting these identities in the quadratic equations, further evaluation will lead to the desired result.

We have the given quadratic equation as:

$\dfrac{{5 + x}}{{5 - x}} - \dfrac{{5 - x}}{{5 + x}} = 3\dfrac{3}{4}$

By rationalization, we get,

$ \Rightarrow \dfrac{{5 + x}}{{5 - x}}\left( {\dfrac{{5 + x}}{{5 + x}}} \right) - \dfrac{{5 - x}}{{5 + x}}\left( {\dfrac{{5 - x}}{{5 - x}}} \right) = \dfrac{{15}}{4}$

$ \Rightarrow \dfrac{{{{(5 + x)}^2} - {{(5 - x)}^2}}}{{(5 + x)(5 - x)}} = \dfrac{{15}}{4}$ … (1)

Now, we know the identities,

${(a + b)^2} = {a^2} + {b^2} + 2ab$

${(a - b)^2} = {a^2} + {b^2} - 2ab$

$({a^2} - {b^2}) = (a - b)(a + b)$

Therefore, by using these identities, we get the equation (1) as

$ \Rightarrow \dfrac{{({{(5)}^2} + 10x + {x^2}) - ({{(5)}^2} - 10x + {x^2})}}{{({{(5)}^2} - {{(x)}^2})}} = \dfrac{{15}}{4}$

$ \Rightarrow \dfrac{{(25 + 10x + {x^2} - 25 + 10x - {x^2})}}{{(25 - {x^2})}} = \dfrac{{15}}{4}$

$ \Rightarrow \dfrac{{20x}}{{(25 - {x^2})}} = \dfrac{{15}}{4}$

Multiplying both sides by $\dfrac{1}{5}$ , we get,

$ \Rightarrow \dfrac{{20x}}{{(25 - {x^2})}} \times \left( {\dfrac{1}{5}} \right) = \dfrac{{15}}{4} \times \left( {\dfrac{1}{5}} \right)$

$ \Rightarrow \dfrac{{4x}}{{(25 - {x^2})}} = \dfrac{3}{4}$

$ \Rightarrow (4x) \times 4 = 3 \times (25 - {x^2})$

$ \Rightarrow 16x = 75 - 3{x^2}$

$ \Rightarrow 3{x^2} + 16x - 75 = 0$

$ \Rightarrow 3{x^2} + 25x - 9x - 75 = 0$

$ \Rightarrow x(3x + 25) - 3(3x + 25) = 0$

$ \Rightarrow (x - 3)(3x + 25) = 0$

Now, either $(x - 3) = 0$

$\therefore x = 3$

Or $(3x + 25) = 0$

$\therefore x = \dfrac{{ - 25}}{3}$

Hence, the roots are $3,\dfrac{{ - 25}}{3}$.

So, the required solution is (a) True.

Note: In order to solve these types of questions, an adequate knowledge of standard identities is needed, after substituting these identities in the quadratic equations, further evaluation will lead to the desired result.

Recently Updated Pages

Three beakers labelled as A B and C each containing 25 mL of water were taken A small amount of NaOH anhydrous CuSO4 and NaCl were added to the beakers A B and C respectively It was observed that there was an increase in the temperature of the solutions contained in beakers A and B whereas in case of beaker C the temperature of the solution falls Which one of the following statements isarecorrect i In beakers A and B exothermic process has occurred ii In beakers A and B endothermic process has occurred iii In beaker C exothermic process has occurred iv In beaker C endothermic process has occurred

The branch of science which deals with nature and natural class 10 physics CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Define absolute refractive index of a medium

Find out what do the algal bloom and redtides sign class 10 biology CBSE

Prove that the function fleft x right xn is continuous class 12 maths CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

What is BLO What is the full form of BLO class 8 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE